HUBUNGAN UKURAN TUBUH TERHADAP BOBOT KARKAS DAN NON KARKAS KAMBING JAWARANDU JANTAN PADA UMUR I2 DAN I3 - Ahmad Komarudin; R.A. Muthalib; Indra Sulaksana (PT. Hasba Edukasi Mandiri, 2026)
This study aims to determine the relationship between body size and carcass and non-carcass weight of male Jawarandu goats at ages I2 and I3. Mat Beken Farm is the source of this data, using Jawarandu goats as research samples. Goats aged (2-2.5) years and (3-3.5) years are known to have permanent incisor replacement, and body measurements include body length, chest girth, shoulder height, carcass weight, and non-carcass weight. The data were analyzed using simple, multiple, and stepwise regression with the help of SPSS software. The results of the study indicate that body size has a significant effect on carcass and non-carcass weight in both age groups, with chest girth being the best indicator.